Implementation of the research method for the assessment of materials intended for contact with water in terms of their susceptibility to biofilm formation in accordance with EN 16421: 2014 - Solecka, Jolanta; Szczotko, Maciej; Maziarka, Dorota; Orych, Izabela; Guśpiel, Adam (Instal, 2021)
The drinking water health safety oversight system does not directly cover installations inside buildings that constitute a significant and materially diverse component of any water distribution system. Low – quality materials can enhance microbial growth on their surface, which can cause numerous health problems for consumers. The presence of biofilm inside installations of buildings may also be associated with the presence of potentially pathogenic bacteria inside of its structure, including: Legionella pneumophila, Pseudomonas aeruginosa or Mycobacterium avium. Effective prevention of secondary microbial contamination of drinking water is possible only through preventive measures, including the assessment and elimination from the use of improper quality products and materials. Low-quality materials can also be a significant source of toxic substances migrating into the water and may adversely affect the sensory assessment of water, including taste, smell, color, turbidity. The paper presents the results of the implementation of the standardized research method according to PN-EN 16421: 2014 Influence of materials on water for human consumption Enhancement of microbial growth (EMG) – Method 3: Measured by mean dissolved oxygen depletion, enabling the assessment of the enhancement of microbial growth by materials intended for contact with drinking water. The 62 samples of various plumbing materials from different producers have been tested and two research methods have been compared. The percentage of differences between the assessment of materials based on the results obtained by standardized method and the custom Polish method for of all tested materials was 8.06%. The implementation of the standardized method is one of the first stages of upgrade and development process of the national system of materials hygienic assessment conducted at the NIPH NIH – NRI to fulfill the requirements of Directive (EU) 2020/2184 of the European Parliament and of the Council of 16 December 2020 on the quality of water intended for human consumption.
Keywords: biofilm; materials intended to come into contact with drinking water; research method; hygienic assessment